Screening of Beta-Secretase Inhibitors by Capillary Electrophoresis-Mass Spectrometry - Schejbal, Jan; Řemínek, Roman; Glatz, Zdeněk (Methods in molecular biology (Clifton, N.J.), 2020)
Alzheimer's disease is the most common cause of dementia, currently afflicting almost 40 million patients worldwide. According to the amyloid cascade hypothesis, the pathogenesis of the disease could be slowed down or even stopped by the inhibition of beta-secretase, making this aspartic acid protease a potentially important drug target site. Capillary electrophoresis is a promising technique for screening putative enzyme inhibitors due to highly effective separations, minuscule sample and other chemicals consumption, compatibility with a variety of detection techniques, and high throughput via automation. This chapter presents a method based on capillary electrophoresis coupled to mass spectrometry detection for kinetic and inhibition assays of the beta-secretase reaction with a decapeptide derived from an amyloid precursor protein.
Keywords: sekretasy; Humans; Mass spectrometry; inhibitory proteas; Beta-secretase; Electrophoresis, Capillary; Amyloid Precursor Protein Secretases; lidé; Alzheimer Disease; Alzheimer’s disease; Alzheimerova nemoc; elektroforéza kapilární; Capillary electrophoresis; Kinetics; Amyloid beta-Protein Precursor; Screening; Mass Screening; inhibitory enzymů; amyloidový prekurzorový protein beta; Enzyme inhibition; plošný screening; aspartátové endopeptidasy; hmotnostní spektrometrie; Aspartic Acid Endopeptidases; Enzyme Inhibitors; Protease Inhibitors; kinetika; Mass Spectrometry